Discussion with representative participants from Meket district on SI-MFS initiative activities implementation - Kidane, Yosef Gebrehawaryat; Tilahun, Mulugeta; Nigir, Bogale; Mengistu, Dejene Kassahun (2022)
Sixteen participants (M=15; F=1) have represented the community in this discussion. The objective of the discussion was to introduce the concepts of Si-MFS initiative to the participants and discuss on possible areas of intervention under this initiative. Furthermore, the role of WTL to link crowdsourcing winner varieties of durum wheat and faba bean to the surrounding farmers. Besides, the project team has discussed with Meket woreda administration and office of Agriculture about the initiative, main agricultural sector problems and designed possible alleviation solutions.